Quantitative analysis of distances covered by professional basketball players according to the movement intensities - Junior, A. C.; Misuta, M. S.; Mercadante, L. A. (International Journal of Sports Science, 2017)
We aimed quantifying distances covered in several intensity categories, based on maximum sprint performed individually in court, during official basketball games. The sample consisted of 12 male professional players in six games. During active game clock, significant difference was found in distances covered only for Z4 intensity zone, with first quarter higher than the second and the fourth quarter, whereas Guards have presented higher values compared to forwards and centers in the Z2 and Z3 intensity zones. During stopped game clock, there was significantly differences among quarters in the Z2 and Z3 intensity zones, whereas guards covered a higher distance in Z1 intensity zone, when compared to forwards and centers. The Z3 intensity zone have presented significantly difference between guards and centers. The practical implications are: distances training in the moderate (21-60% of velpeak) and submaximal (61-80% of velpeak) intensity need to be differentiated individually by playing position. More attention is required to intensities that players are exposed during stoppage periods, not exceeding 20% of their individual maximum velocity. The third quarter are more likely to players to perform lower intensity activities during recovery. Provide special attention and guidelines to forwards and centers for their recovery during stopped game clock.